Evaluation of glycoprotein B genotypes and load of CMV infecting blood leukocytes on prognosis of AIDS patients - Aldo Albuquerque Cunha; Vitor Hugo Aquino; Viviane Mariguela; Maurício Lacerda Nogueira; Luiz Tadeu Moraes Figueiredo (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
BACKGROUND: Cytomegalovirus (CMV) remains an important pathogen to immunocompromised patients even in the era of HAART. The present study aimed at evaluating the influence of CMV viral load and its gB genotypes on AIDS patients' outcome. METHODS: Blood samples of 101 AIDS patients were collected and tested for HIV load, CD4 - cell count and opportunistic pathogens, including CMV. Semi-nested PCRs were run to detect CMV genome and in the positive samples, gB genotyping and CMV load were established using enzymatic restriction and real time PCR, respectively. All patients were clinically followed for four years. RESULTS: In thirty patients (31%) CMV was detected and all fatal cases (n = 5) occurred in this group of patients (p = 0.007), but only two patients had CMV disease (1.9%). However, viral load was not statistically associated with any analyzed parameter. The most frequently observed CMV genotype was gB2 (45.16%) followed by gB3 (35.48%). gB2 genotype was more frequently found in patients with CD4-cell counts under 200 cells/mm³ (p = 0.0017), and almost all fatal cases (80%) had gB2 genotype. CONCLUSIONS: Our study suggests that CMV and its polymorphisms in biologically relevant genes, such as the gB encoding ORF, may still influence the prognosis and outcome of AIDS patients. The gB2 genotype was associated to patient's bad outcome.